Quantitative Distribution of ‘ Candidatus Liberibacter asiaticus’ in Citrus Plants with Citrus Huanglongbing - Li, Wenbin; Levy, Laurene; Hartung, John S. (Phytopathology, 2009)
Citrus huanglongbing (HLB), or greening disease, is strongly associated with any of three nonculturable gram-negative bacteria belonging to ‘Candidatus Liberibacter spp.’ ‘Ca. Liberibacter spp.’ are transmitted by citrus psyllids to all commercial cultivars of citrus. The diseases can be lethal to citrus and have recently become widespread in both São Paulo, Brazil, and Florida, United States, the locations of the largest citrus industries in the world. Asiatic HLB, the form of the disease found in Florida, is associated with ‘Ca. Liberibacter asiaticus’ and is the subject of this report. The nonculturable nature of the pathogen has hampered research and little is known about the distribution of ‘Ca. L. asiaticus’ in infected trees. In this study, we have used a quantitative polymerase chain reaction assay to systematically quantify the distribution of ‘Ca. L. asiaticus’ genomes in tissues of six species of citrus either identified in the field during survey efforts in Florida or propagated in a greenhouse in Beltsville, MD. The populations of ‘Ca. L. asiaticus’ inferred from the distribution of 16S rDNA sequences specific for ‘Ca. L. asiaticus’ in leaf midribs, leaf blades, and bark samples varied by a factor of 1,000 among samples prepared from the six citrus species tested and by a factor of 100 between two sweet orange trees tested. In naturally infected trees, above-ground portions of the tree averaged 10 10 ‘Ca. L. asiaticus’ genomes per gram of tissue. Similar levels of ‘Ca. L. asiaticus’ genomes were observed in some but not all root samples from the same plants. In samples taken from greenhouse-inoculated trees, levels of ‘Ca. L. asiaticus’ genomes varied systematically from 10 4 genomes/g at the graft inoculation site to 10 10 genomes/g in some leaf petioles. Root samples from these trees also contained ‘Ca. L. asiaticus’ at 10 7 genomes/g. In symptomatic fruit tissues, ‘Ca. L. asiaticus’ genomes were also readily detected and quantified. The highest levels of ‘Ca. L. asiaticus’ in fruit tissues were found in the locular membranes and septa (10 8 genomes/g), with 100-fold lower levels of ‘Ca. L. asiaticus’ in the meso and pericarp of such fruit. Our results demonstrate both the ubiquitous presence of ‘Ca. L. asiaticus’ in symptomatic citrus trees as well as great variation between individual trees and among samples of different tissues from the same trees. Our methods will be useful in both the management and scientific study of citrus HLB, also known as citrus greening disease.